Effect of intravenous lignocaine infusion on propofol requirement using a closed-loop anaesthesia delivery system: A randomised controlled study - Jijo Francis; Goverdhan D. Puri; Tanvir Samra; Vighnesh Ashok; Rajarajan Ganesan (Indian Journal of Anaesthesia)
Background and Aims: Closed-loop anaesthesia delivery systems (CLADS) have made total intravenous anaesthesia easier, safer and more precise. lignocaine is a local anaesthetic with analgesic properties. This study aimed to compare the consumption of propofol and fentanyl delivered using CLADS in patients administered intraoperative lignocaine infusion. Methods: In this randomised trial, 70 females (18–60 years) undergoing elective breast surgery between March 2021 and December 2022 were randomised into two groups: a group administered lignocaine (1.5 mg/kg bolus followed by infusion of 2 mg/kg/h) and a placebo group. In both groups, propofol was administered using CLADS with a target bispectral index (BIS) set at 50 and an initial set fentanyl concentration of 2 ng/ml. The data were analysed using measures of central tendency and dispersion. Results: The mean total consumption of propofol (mg/kg/h) was 6.0 [standard deviation (SD): 1.4] [95% confidence interval (CI): 5.54, 6.46] in the lignocaine group and 6.2 (SD: 1.7) (95% CI: 5.64, 6.76) in the placebo group (P = 0.719). The mean dose of propofol (mg/kg) to achieve target BIS of 50 at induction was 2.00 (SD: 0.39) (95% CI: 1.87, 2.13) in the lignocaine group and 1.95 (SD: 0.38) (95% CI: 1.82, 2.08) in the placebo group (P = 0.515). The total dose of intraoperative fentanyl, as well as the performance parameters of CLADS (Median Performance Error, Median Absolute Performance Error and Wobble), time to extubation, time to rescue analgesia and duration of post-anaesthesia care unit stay were similar in both groups. Conclusion: There were no significant additive anaesthetic or analgesic effects of intraoperative lignocaine given during breast surgery, where anaesthesia was maintained with propofol, fentanyl and nitrous oxide.